Prediction of fetal growth restriction using estimated fetal weight vs a combined screening model in the third trimester. (5th November 2017) - Miranda, J.; Rodriguez‐Lopez, M.; Triunfo, S.; Sairanen, M.; Kouru, H.; Parra‐Saavedra, M.; Crovetto, F.; Figueras, F.; Crispi, F.; Gratacós, E.
ABSTRACT: Objectives: To compare the performance of third‐trimester screening, based on estimated fetal weight centile (EFWc) vs a combined model including maternal baseline characteristics, fetoplacental ultrasound and maternal biochemical markers, for the prediction of small‐for‐gestational‐age (SGA) neonates and late‐onset fetal growth restriction (FGR). Methods: This was a nested case–control study within a prospective cohort of 1590 singleton gestations undergoing third‐trimester (32 + 0 to 36 + 6 weeks' gestation) evaluation. Maternal baseline characteristics, mean arterial pressure, fetoplacental ultrasound and circulating biochemical markers (placental growth factor (PlGF), lipocalin‐2, unconjugated estriol and inhibin A) were assessed in all women who subsequently delivered a SGA neonate ( n  = 175), defined as birth weight < 10 th centile according to customized standards, and in a control group ( n  = 875). Among SGA cases, those with birth weight < 3 rd centile and/or abnormal uterine artery pulsatility index (UtA‐PI) and/or abnormal cerebroplacental ratio (CPR) were classified as FGR. Logistic regression predictive models were developed for SGA and FGR, and their performance was compared with that obtained using EFWc alone. Results: In SGA cases, EFWc, CPR Z ‐score and maternal serum concentrations of unconjugated estriol and PlGF were significantly lower, while mean UtA‐PI Z ‐score and lipocalin‐2 and inhibin A concentrations were significantly higher, compared with controls. Using EFWc alone, 52% (area under receiver–operating characteristics curve (AUC), 0.82 (95% CI, 0.77–0.85)) of SGA and 64% (AUC, 0.86 (95% CI, 0.81–0.91)) of FGR cases were predicted at a 10% false‐positive rate. A combined screening model including a‐priori risk (maternal characteristics), EFWc, UtA‐PI, PlGF and estriol (with lipocalin‐2 for SGA) achieved a detection rate of 61% (AUC, 0.86 (95% CI, 0.83–0.89)) for SGA cases and 77% (AUC, 0.92 (95% CI, 0.88–0.95)) for FGR. The combined model for the prediction of SGA and FGR performed significantly better than did using EFWc alone ( P < 0.001 and P  = 0.002, respectively). Conclusions: A multivariable integrative model of maternal characteristics, fetoplacental ultrasound and maternal biochemical markers modestly improved the detection of SGA and FGR cases at 32–36 weeks' gestation when compared with screening based on EFWc alone. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.